Effect of Soil Fertility on the Growth Characteristics of Two Young Trees of the Neem Family - Wang, Wenyi; Ma, Cong; Wang, Yanhong (International Journal of Agriculture and Food Sciences Research, 2024)
To select tree species suitable for growth under Chinese ephedra forests, this study set up three soil fertility treatments: pure sandy soil, V (sand): V (fertilizer) = 3:1, and V (sand): V (fertilizer) = 1:1, to investigate the effects of different soil fertility levels on the growth characteristics of two tree species, Azadirachta indica A. Juss (neem) and Melia azedarach (chinaberry). The results show that: (1) Under low light conditions and pure sandy soil, the height and basal diameter of neem significantly increased, while chinaberry showed a significant increase in height and basal diameter under the V (sand): V (fertilizer) = 1:1 condition. (2) Under the V (sand): V (fertilizer) = 1:1 condition, both neem and chinaberry exhibited maximum leaf growth characteristics, while there was a decreasing trend under the V (sand): V (fertilizer) = 3:1 condition. These results indicate that neem is more suitable for growth in pure sandy soil and is more tolerant to poor soil conditions, while chinaberry thrives under the V (sand): V (fertilizer) = 1:1 condition. This preliminary selection provides a theoretical basis for the initial screening of tree species for coastal defense forests.